Impact of microbial contamination of the islet product during total pancreatectomy with islet autotransplantation. (12th February 2020) - Kumano, Kenjiro; Takita, Morihito; Vasu, Srividya; Darden, Carly; Lawrence, Michael; Beecherl, Ernest; Gupta, Amar; Onaca, Nicholas; Naziruddin, Bashoo
Abstract: Background: The combined use of interleukin‐1β and tumor necrosis factor–α blockers in the peritransplant period has improved outcomes of total pancreatectomy with islet autotransplantation (TPIAT). However, these drugs may suppress the immune system, resulting in severe infection. Methods: We retrospectively investigated the impact of microbial‐contaminated islet product on posttransplant complications and metabolic outcomes of TPIAT patients receiving the IL‐1β and TNF‐blockade treatment at our center. Results: Among 108 TPIAT patients, 37 patients (34%) received contaminated products. Preoperative stent treatment and fibrosis score were independent risk factors for the contamination. There were no significant differences between the contaminated and noncontaminated product groups in posttransplant infectious complication rate, length of hospitalization, or readmission rate. However, islet equivalents ( P < .0001) and insulin independence rate ( P = .036) at 6 months were significantly lower for patients receiving contaminated product. Conclusions: These results suggest that combined anti‐inflammatory drug use is safe and well tolerated in TPIAT patients who receive contaminated islet product and does not increase the rate of infectious complications; however, contaminated islet product is associated with poor metabolic outcomes. Abstract : Highlight Kumano and colleagues analyzed data from 108 patients undergoing total pancreatectomy with islet autotransplantation (TPIAT) and reported that preoperative stent treatment and pancreas fibrosis score were independent risk factors for contamination of the islet product. They recommended earlier TPIAT approach rather than endoscopic intervention for better metabolic outcomes.